Gasotransmitters: a review - Natarajan, Anusha; G., Jefry Winner (International Journal of Basic & Clinical Pharmacology, 2023)
The gaseous molecules produced endogenously with several physiological functions are called gasotransmitters. Even though initially, they were predominantly thought to be of neuronal origin, recent research has clarified that they have roles far beyond that. Their primary function is maintaining the integrity of the cardiovascular system and many other parts. From the available knowledge, we have just started to learn about their roles in physiological systems that could be translated to pharmacological drug development and therapeutics. Most of the process that remains in the form of preclinical research has to go a long way toward utilizing them in therapeutics. This review addresses the various levels at which they could be potentially exploited as therapeutics and their recent entry into clinical trials.